Phylogenetic Endemism Hotspots of North American Birds Are Associated With Warm Temperatures and Long- and Short-Term Climate Stability - Acevedo, Sebastian; Sandel, Brody (Frontiers in Ecology and Evolution, 2021)
Human activities have dramatically altered the distribution and abundance of species, and our impacts are likely to increase in the near future. Conservation efforts are typically faced with scarce resources, forcing us to prioritize areas based in part on estimates of their conservation value. Two major factors in conservation value are a species uniqueness and its extinction risk. Though these ideas are multidimensional, one important component of uniqueness is evolutionary distinctness, while risk is strongly related to geographic range size. These components are combined in an assemblage-level measure called phylogenetic endemism (PE), which measures the degree to which the species in an assemblage are small-ranged and phylogenetically distinct. Broad-scale patterns and correlates of PE are becoming better known for a variety of groups, and have been shown to depend on current climate, geographic isolation and long-term climate stability. Human impacts (e.g. land cover changes), are likely to shape PE as well, though the coarse resolution of most previous studies may make this difficult to detect. Overall, PE patterns at fine spatial and temporal resolutions are not well understood. Here, we fill this gap using data from the North American Breeding Bird Survey. These data comprise a long-term annual record with fine spatial resolution and near-continental extent. We assess geographic patterns and trends in PE, and relate these to a range of putative predictor variables including measures of current climate, land cover, long-term and recent climate change. Bird PE is concentrated in three main hotspots: the west coast, the southeast and south-central Canada east of the Rockies. High PE values tended to occur in regions with high temperatures and stability in temperature. PE patterns are driven more strongly by patterns of range size than phylogenetic distinctiveness, and are trending gradually upward, driven by increasingly frequent sightings of small-ranged species. These results indicate the importance of climate stability on multiple time scales in influencing endemism patterns and suggest a surprisingly minor influence of direct human land use. The increase in PE through time may reflect successful conservation efforts that have led to population recoveries of some small-ranged species.